Production and operations management systems - Gupta, Sushil
"This text provides an understanding of the manufacturing and operations functions as well as the processes of goods and service producers. Illustrating how operations relate to the rest of the organization, it will help readers develop a sense of managerial competence in making decisions in the design, planning, operation and control of manufacturing, production, and operations systems through examples and case studies. The text uses analytical techniques when necessary to develop critical thinking and to sharpen decision making skills. An accompanying website offers slides, lectures, Excel worksheets, and solutions to short and extended problem sets"--